Parental Leave and Discrimination in the Labor Market - Julia Schmieder; Doris Weichselbaumer; Clara Welteke; Katharina Wrohlich (Institute of Labor Economics (IZA), 2024)
Promoting fathers to take parental leave is seen as a promising way to advance gender equality. However, there is still a very limited understanding of its impact on fathers' labor market outcomes. We conducted a correspondence study to analyze whether fathers who take parental leave face discrimination during the hiring process in three different occupations. Fathers who took parental leave in a female-dominated or gender-neutral occupation are not less likely to be invited to a job interview compared to fathers who did not take leave. However, in the male-dominated occupation, fathers who have taken long parental leave are penalized. Regardless of leave-taking, fathers are treated less favorably than mothers in the female-dominated and the gender-neutral occupation, while the opposite is true for the male-dominated occupation. This suggests the presence of strong gender norms concerning the perception of ideal employees in different occupations.
Keywords: C93; J13; J71; 330; discrimination; parental leave; gender; hiring; experiment